The Role of Extended Families in Improving Education in Eastern Division Fort Portal City. - Nyamugwa, Benard (Kabale University, 2023)
The study investigated the role of extended families in improving education in areas of Eastern Division, Fort Portal City. The following objectives guided the study; to investigate the role of extended families in helping family members (children) acquire the necessary skills and knowledge in various activities to produce self-reliant individuals. To investigate whether extended families could be used to restructure the present curriculum so that practical work is emphasized to produce job creators. Findings show that the researcher established that all children who were staying in extended families were being taught various skills such as fetching water (mostly), looking after the young ones, digging in gardens, and fetching firewood. Further findings showed that some adults from extended families helped to mold the behavior of the children under their care. Some of these adoptive parents however saw importance in this practice. Findings also showed that the majority of the teachers tried to provide practical activities to learners during class days; almost all teachers claimed that they offered agriculture as a subject at school. However, fewer teachers claimed that they offered agriculture as a subject at school. However, fewer teachers agreed that they made provision for community service, and neither did they concur that they invited resource people to school. Recommendations were made like the government needs to sensitize the population about the importance of work and its fruits and benefits. The curriculum has to be restructured and accommodate even these practical and moral activities. The government through focal council leaders should sensitize especially those living in extended families about their roles in restructuring the present curriculum.